Răspunsuri

2014-09-20T09:36:20+03:00
2a+b = 24    2b+c = 27    2c +a =30  adunăm aceste 3 relații și obținem ⇒ 3a+3b +3c = 81  ⇒  3×(a+b+c) = 81    ⇒  a+b+c = 81÷3      a+b+c = 27  din prima relație  b=24-2a   iar din a 2-a  c=27 -2b = 27-2(24-2a)  înlocuim în releția:   a+b+c =27  ⇒ a+( 24-2a )+[27- 2(24-2a)]=27  ⇒   a+(24-2a)=27-[27-2(24-2a)]adica,  a+(24-2a) =27 - 27 +2(24-2a)  a+(24-2a)=2(24-2a) ⇒ a+(24-2a) = (24-2a) + (24-2a)  ⇒a=24-2a  ⇒ 24 =a+2a =3a ⇒ a = 8       b=24 -2×8 =24-16   b=8   c = 27 - 16   c = 11